Literacy Enhancement for Promoting the Cikareumbi Tomato War Festival as a Post-Pandemic Sundanese Cultural Tradition - Kurnia Putri, Sheila; Shauma Silmi Faza; Arif Budiman (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
This study analyzes the role of digital literacy in revitalizing the Perang Tomat (Tomato War) tradition in Cikareumbi Village during the post-pandemic period. The program employed a Participatory Action Research (PAR) methodology, engaging artists, youth, and community elders in training on digital content related to cultural branding and creative media production. Participants were trained to create cultural content with smartphones, manage social media accounts, and reinterpret digital platforms as instruments for cultural representation. Empirical evidence indicates notable enhancements in the digital capacity of the community. The Instagram insights for the newly established “Mekar Budaya Lembang” account indicate 3,299 views and 128 interactions over the course of one month, with 61.3% of viewers classified as non-followers. Furthermore, 85% of participants demonstrated proficiency in content creation, 78% acquired skills for independent media management, and 60% grasped the principles of cultural branding. The findings indicate that digital literacy enables individuals to narrate stories within their communities and enhances the visibility of Perang Tomat beyond its local context. The study concludes that digital literacy serves as both a technical skill and a cultural strategy, enhancing community agency and promoting cultural sustainability. This model of community-based digital empowerment provides a replicable framework for the promotion of intangible heritage in digitally mediated contexts.